Review and scan of core municipal public engagement principles - Jamal, Shaila; Warren, Rachel; Razzaque, Pierce; MacBeath, Victoria (Prepared by the McMaster Research Shop for City of Hamilton, Government and Community Relations, 2022)
The City of Hamilton’s Public Engagement Charter specifies eight Core Principles of Public Engagement that set the tone and direction for successful City-led engagement practices. This charter was co-developed with community stakeholders in 2014. Given that a significant amount of time has expired since the creation of the charter, the purpose of this project was to conduct an environmental scan to identify the core principles of public engagement commonly adopted by comparative municipalities across Canada and, using this information, recommend opportunities for Hamilton to inform the update of their charter. This report provides findings from the environmental scan, including an analysis of the relevancy and comprehensiveness of the City of Hamilton’s existing public engagement charter.
Keywords: Hamilton, community-engaged research, community engagement principles, environmental scan, municipal engagement, public consultation